2010
DOI: 10.3109/09546630903401462
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose 1064-nm Q-switched Nd:YAG laser for the treatment of melasma

Abstract: Low-dose 1064-nm QSNYL appears to be an effective treatment modality for melasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 18 publications
(25 reference statements)
1
48
0
6
Order By: Relevance
“…The recurrence rates in previous studies ranged from 0% to 67%. [6][7][8][9][10][11][12][13][14] In this study, recurrence was limited to 24.1% of patients, with partial recurrence in almost all lesions. All recurrent CALMs underwent complete remission after an additional 3 or 4 treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence rates in previous studies ranged from 0% to 67%. [6][7][8][9][10][11][12][13][14] In this study, recurrence was limited to 24.1% of patients, with partial recurrence in almost all lesions. All recurrent CALMs underwent complete remission after an additional 3 or 4 treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Only a single case report on CALM treatment has appeared to date. 19 The clinical efficacy of low-fluence Q-switched Nd:YAG lasers requires further exploration.…”
mentioning
confidence: 99%
“…The fluence was between 2.0-3.5 j/cm . Another study with the same laser by Choi [21] et al has showed that the mean MASI scores were significantly decreased after five sessions with 1-week interval. The fluence was also 2.0-3.5 j/cm .…”
Section: Lasers and Light Sourcesmentioning
confidence: 88%
“…Recently the subthermolytic Q-switched Nd Yag laser therapy has been widely used because of its efficacy and safety even in Asian patients with darker skin tone (15). Although subthermolytic Q-switched 1064nm Nd Yag laser therapy has shown promising results, this treatment would require multiple sessions on a weekly basis, which would burden the patients (16,17). In addition, there are some reports of confetti-like hypopigmentation occurring after multiple treatment sessions (18,19).…”
Section: Introductionmentioning
confidence: 99%